2006
DOI: 10.1080/17477160600962864
|View full text |Cite
|
Sign up to set email alerts
|

Muscular strength and cardiorespiratory fitness is associated with higher insulin sensitivity in children and adolescents

Abstract: Muscular strength has been identified for the first time as an independent and powerful predictor of better insulin sensitivity in children. Lower strength, CRF and higher central adiposity are highly predictive of higher levels of insulin resistance in this cohort, and should be considered potential targets for interventions designed to enhance metabolic fitness in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 45 publications
11
105
2
10
Order By: Relevance
“…6 Recently we found in 10-to 15-year-old children that higher upper body strength and lower waist circumference were independently associated with better insulin sensitivity. 13 In addition, we found that both muscular strength and cardiorespiratory fitness (CRF) provided protection from higher insulin resistance in this cohort, 13 as reported in recent adult data. 11 High intensity resistance training may provide equal or greater metabolic benefit than other forms of exercises.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…6 Recently we found in 10-to 15-year-old children that higher upper body strength and lower waist circumference were independently associated with better insulin sensitivity. 13 In addition, we found that both muscular strength and cardiorespiratory fitness (CRF) provided protection from higher insulin resistance in this cohort, 13 as reported in recent adult data. 11 High intensity resistance training may provide equal or greater metabolic benefit than other forms of exercises.…”
Section: Introductionsupporting
confidence: 76%
“…We arranged all gas exchange data in 30-s intervals for analysis with VO 2 peak determined as the highest value of O 2 consumption measured during the test. 13,37 Maximal muscular strength was measured using a progressive repetition maximal lift (1RM) protocol as follows: familiarization phase where participants were instructed on correct form and breathing and given 2-3 practice lifts with a light bar or no weight for the leg press; a warm-up phase of three lifts with weights selected to elicit a RPE on the Borg scale (6-20) of 15 by lift 3; a testing phase where lifts were progressively increased until the weight could not be lifted, despite verbal encouragement, on two consecutive attempts 90 s apart. There was a rest period of 60-90 s between lifts with 1RM determined in approximately 6-10 lifts.…”
Section: Fitness Parametersmentioning
confidence: 99%
“…(11,12) se describió por vez primera el índice general de fuerza (IGF), a partir de la estandarización de los resultados obtenidos de la fuerza de prensión manual (en kg) y el salto de longitud (en cm). Este índice demostró en niños y adolescentes europeos una asociación inversa con el perfil de riesgo lipídico-metabólico (13), la concentración de proteínas inflamatorias (14), los niveles de presión sanguínea (15) y la sensibilidad a la insulina (16), entre otros.…”
Section: Introductionunclassified
“…Cependant, différentes formes d'activité physique peuvent influencer directement la résistance à l'insuline en provoquant, entre autres, une activation à court terme des transporteurs de glucose (GLUT-4) et de leurs récepteurs [24], en abaissant le taux circulant d'insuline [30,31] et en augmentant la production des facteurs anti-inflammatoires tels que l'adiponectine [32,33] ou encore en induisant des modifications myofibrillaires appropriées (dont une augmentation de la quantité de fibres oxydatives et insulinosensibles) [34]. Ces effets peuvent être directs ou secondaires à une augmentation de l'aptitude physique [21,29,35] ou à une nécessaire baisse d'adiposité (en relation avec une augmentation de la concentration d'adiponectine circulante) [27,36,37]. Comme l'indique la Figure 1, la cible principale des programmes d'activité physique devrait être l'insulino-résistance (qui est un paramètre prépondérant du syndrome métabolique), même si une activité physique régulière peut directement agir sur les autres facteurs que sont la pression artérielle [38][39][40][41] ou la lipidémie [38,42].…”
Section: Données éPidémiologiquesunclassified